Merajut Kebhinekaan dalam Pendidikan Beragama di Tengah Bangsa Pluralitas - Dewi Nurany, Alma Livia; Hidayati, Latifah Nurul; Zulaika, Rida; Hanindraswari, Annisa Dwi Mukarromah; Akbar, Muhammad Najib (Lembaga Yasin AlSys, 2022)
Indonesia as a multi-ethnic, cultural and religious country is a necessity that cannot be denied by anyone. Diversity in this country is no reason for division. The basis for the existence of religion and belief means that every religion believes in the support of the state to carry out its own worship. This can be found in the concept of the Indonesian motto, namely Bhineka Tunggal Ika, which has different meanings but has one goal. The research method is carried out through library research or library research. The purpose of this study is to determine the integration of religion in pluralism. Our findings show that in Indonesia's many different cultures, adherents of different religions can also show mutual tolerance, upholding each other's cultures without demeaning other cultures.